Pharmacists prescribing COVID-19 therapeutics (nirmatrelvir/ritonavir) in a community pharmacy: An observational time and motion study - Joung, Yelim; Dang, Richard H.; Hormozian, Michelle; Chacon, Allison; Mack, Wendy (JAPhA practice innovations, 2025)
Nirmatrelvir/ritonavir (NMV/r) (Paxlovid) was the first oral therapeutic agent available for outpatient treatment of mild-to-moderate coronavirus disease 2019, reducing morbidity and mortality. As part of the emergency use authorization (EUA), pharmacists were granted the authority to prescribe NMV/r subject to the conditions and eligibility criteria of the EUA. Owing to the additional steps required for pharmacists to prescribe NMV/r, widespread adoption of pharmacist-led NMV/r services may have been hindered. This study aimed to assess the feasibility of a pharmacist-led NMV/r prescribing service by quantifying the procedural time spent to prescribe NMV/r and to identify obstacles to service integration. A direct observational time-motion study of a pilot program was conducted at a community pharmacy in an academic medical center in Southern California from December 1, 2022, to March 31, 2023. Each encounter was tracked from the initial patient request to the prescription of NMV/r, and the time spent to complete each step was recorded. Data were collected using the Research Electronic Data Capture tool. Twenty-two patients were observed, 8 of whom were eligible for NMV/r. The median time from patient outreach to prescription generation was 22 minutes (interquartile range [IQR] = 15, 84) and 5 minutes (IQR = 3, 11) for referral to a physician for ineligible patients. Patient screening to comply with the EUA criteria took 10 minutes (IQR = 7, 10) for eligible patients and 4 minutes (IQR = 2, 6) for ineligible patients. Barriers such as multitasking and the mode of initial patient outreach affected or delayed service provision. This study suggests that the NMV/r prescribing service adds a manageable amount of time to pharmacist workflow at this site, comparable with other clinical services in pharmacy settings. Feasibility may vary depending on the pharmacy setting and patient volume.